Pengaruh Pajak Hiburan, Pajak Reklame, Pajak Bumi Dan Bangunan, Dan Pajak Restoran Terhadap Pendapatan Asli Daerah Kota Surabaya - Muhammad Sigro Amurwatpraja; Sri Trisnaningsih (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the influence of entertainment tax, advertisement tax, land and building tax, and restaurant tax on the Regional Original Revenue (PAD) of Surabaya City. The background of this research is based on the importance of optimizing the regional tax sector as one of the main sources in enhancing regional fiscal independence, particularly in Surabaya. This study uses a quantitative approach with the Structural Equation Modeling (SEM) technique using Partial Least Squares (PLS) through SmartPLS 4.0 software. The data used are secondary data obtained from the regional revenue realization reports of Surabaya City for the period of 2021 to 2023. The independent variables in this study include entertainment tax, advertisement tax, land and building tax, and restaurant tax, while the dependent variable is the Regional Original Revenue (PAD). The results show that advertisement tax and land and building tax have a positive and significant effect on PAD in Surabaya. Meanwhile, entertainment tax and restaurant tax do not have a significant effect on PAD. These findings indicate that although the entertainment and restaurant sectors have high revenue potential, their contribution to PAD is still not optimal. This may be due to low taxpayer compliance, incomplete tax object data collection, and limited supervision by the authorities in managing the tax potential from these sectors.